Jurnal Akuntansi, Manajemen Dan Ekonomi 2018
DOI: 10.32424/1.jame.2018.20.2.1226
|View full text |Cite
|
Sign up to set email alerts
|

The impact of education, training and work experience on job satisfaction and job performance (Study on Bank BRI Purbalingga)

Abstract: The purpose of this research is to confirm and integrate the Duggan & Horton (2004) and Robbins (2005) founding on the effect of career development on job satisfaction, and the impact of job satisfaction on employee performance. Existing literatures and researches are only talking about the influence of both career development and job satisfaction as independent variables on employee performance. The sample of this research was 80 employees from Bank Rakyat Indonesia (BRI) in Purbalingga. Those samples are det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, the results of the survey conducted in 2018 on 80 Indonesian bank staffs showed that the regression coefficient between the two is positive, i.e., there is a positive correlation between the employees' work experience and job satisfaction. The results show that for every one percentage point increase in the work experience of bank employees, job satisfaction will increase by 0.202 percentage points [18]. The reason for this difference may due to the characteristics of the industry.…”
Section: Work Experience and Job Satisfactionmentioning
confidence: 96%
“…However, the results of the survey conducted in 2018 on 80 Indonesian bank staffs showed that the regression coefficient between the two is positive, i.e., there is a positive correlation between the employees' work experience and job satisfaction. The results show that for every one percentage point increase in the work experience of bank employees, job satisfaction will increase by 0.202 percentage points [18]. The reason for this difference may due to the characteristics of the industry.…”
Section: Work Experience and Job Satisfactionmentioning
confidence: 96%